Pengaruh Perceived Organizational Support terhadap Work Engagement Guru Sekolah Dasar Swasta X - Rafly Nurhuda; Agus Budiman (Bandung Conference Series: Psychology Science, 2022)
Abstract. Work engagement is a study concept that explains an employee engagement in a positive, fulfilling, and state of mind related to the work they do. In predicting work engagement, there are job demands and job resources. One that can act as a job resource to balance job demands is perceived organizational support which is a common belief formed by each employee regarding their assessment which is formed based on their experience of organizational policies and procedures, acceptance of resources, interaction with supervisors, and about the organization's concern for their well-being. The study aims to determine the effect of perceived organizational support on work engagement in private elementary school teachers X. The study method used is quantitative approach with causality design. The number of subjects in this study was 49 private elementary school teachers X. The measuring instruments used SPOS to measure perceived organizational support and UWES-9 to measure work engagement. The results of this study show that 56% of teachers have a high level of perceived organizational support and 58% teachers have a high level of work engagement. This study used multiple regression data analysis with the result of R2 = 0,949 and partial coeffitient of determination test with the result of the Evaluative Judgements component had the highest influence with a value of β = 0,966. Concluded that the Evaluative Judgements component has the higher influence in bringing up the work engagement of private elementary school teachers X. Abstrak. Work engagement merupakan konsep kajian yang menjelaskan sebuah keterlibatan karyawan secara positif, fulfilling, dan keadaan pikiran yang berkaitan dengan pekerjaan yang dilakukannya. Dalam memprediksi work engagement terdapat job demands dan job resources. Salah satu yang dapat berperan sebagai job resources untuk menyeimbangi job demands terdapat perceived organizational support yang merupakan keyakinan umum yang dibentuk oleh tiap karyawan mengenai penilaian mereka yang dibentuk berdasarkan pada pengalaman mereka terhadap kebijakan dan prosedur organisasi, penerimaan sumber daya, interaksi dengan atasan, dan mengenai kepedulian organisasi terhadap kesejahteraannya. Penelitian bertujuan untuk mengetahui pengaruh perceived organizational support terhadap work engagement pada guru SD swasta X. Metode penelitian yaitu kuantitatif kausalitas. Subjek dalam penelitian ini yaitu 49 guru. Alat ukur menggunakan SPOS untuk mengukur perceived organizational support dan UWES-9 untuk mengukur work engagement Scale. Hasil penelitian ini menunjukkan bahwa 56% guru memiliki tingkat perceived organizational support yang tinggi dan 58% guru memiliki tingkat work engagement yang tinggi. Penelitian ini menggunakan analisis data regresi berganda dengan hasil R2 = 0,949 dan uji koefisien determinasi parsial dengan hasil komponen evaluative judgements memiliki pengaruh paling besar yaitu dengan nilai β = 0,966. Maka dapat disimpulkan bahwa komponen evaluative judgements memiliki pengaruh paling besar dalam memunculkan work engagement guru SD swasta X.